Degradation of reactive blue 19 using electrochemical peroxidation process application of a 23 full factorial design - Austero, Sheila B. (2010)
Water quality is a major concern around the world due to the limited amount of freshwater available for household and commercial use. There has also been an increasing contamination in water systems. One group of contaminants meriting much attention is the synthetic organic pollutants which include dyes, pesticides, pharmaceutical and personal care products. For this study, the degradation of CI Reactive Blue 19 dye using electrochemical peroxidation was evaluated with a 23 full factorial design augmented with four centerpoints. The factors and levels of the experimental design were as follows: initial pH (2.2, 2.5, 2.8), initial H2O2 dosage (332 mM, 377 mM, 422 mM), and current (0.60 A, 0.90 A). Results of the study showed that initial pH and initial pH-current interaction significantly influenced the percent COD removal. Moreover after 60 minutes of treatment, the percent absorbance reduction reached up to 99.98% and the percent COD removal reached up to 82.83%.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Electrochemical peroxidation